2016
DOI: 10.1007/s11255-016-1303-2
|View full text |Cite
|
Sign up to set email alerts
|

Carbachol-induced signaling through Thr696-phosphorylation of myosin phosphatase-targeting subunit 1 (MYPT1) in rat bladder smooth muscle cells

Abstract: Purpose Lines of evidence suggest that Rho-associated protein kinase (ROCK) mediated myosin phosphatase targeting subunit 1 (MYPT1) phosphorylation play a central role in smooth muscle contraction. However, the physiological significance of MYPT1 phosphorylation at Thr696 catalyzed by ROCK in bladder smooth muscle remains controversial. We attempt to directly observe the quantitative protein expression of RhoA/ROCK and phosphorylation of MYPT1 at Thr696 after carbachol administration in rat bladder smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Thus, P‐MYPT‐1 is a reflection of RhoA/Rho‐kinase pathway activity, and its excessive levels in GSNOR −/− mouse bladders conceivably lead to excessive smooth muscle contraction and detrusor overactivity. A previous study reported that carbachol activates the RhoA/Rho‐kinase pathway, leading to MYPT‐1 phosphorylation at Thr‐696 and sustained contraction in rat bladder smooth muscle cells . In our present study, basal expression levels of the RhoA/Rho‐kinase pathway were unchanged, but the increased level of phospho‐MYPT‐1 is consistent with increased activity of this pathway.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, P‐MYPT‐1 is a reflection of RhoA/Rho‐kinase pathway activity, and its excessive levels in GSNOR −/− mouse bladders conceivably lead to excessive smooth muscle contraction and detrusor overactivity. A previous study reported that carbachol activates the RhoA/Rho‐kinase pathway, leading to MYPT‐1 phosphorylation at Thr‐696 and sustained contraction in rat bladder smooth muscle cells . In our present study, basal expression levels of the RhoA/Rho‐kinase pathway were unchanged, but the increased level of phospho‐MYPT‐1 is consistent with increased activity of this pathway.…”
Section: Discussionsupporting
confidence: 83%
“…The underlying mechanism of sustained contraction is related to MYPT1 [ 13 ]. Multiple lines of evidence imply that MYPT1 may regulate the biochemical activity of MLCP through multiple mechanisms, thereby regulating MLC phosphorylation and affecting bladder smooth muscle detrusor contraction [ 14 ]. These results suggest that the pathogenesis of DBD may be closely related to MLC phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…DKK2 is generally considered to be a direct inhibitor of Wnt binding to the LRP5/LRP6 coreceptor of FZD [56]. In addition, decreased DKK2 expression is seen in melanoma cell lines and tumors [57,58]. Thirdly, Axin2 has similar biochemical and cell biological properties to Axin.…”
Section: Discussionmentioning
confidence: 99%